3D Visualization For Augmented Reality In ‘Jajanan Pasar’ Puzzles - Jessica Carlina (ULTIMART Jurnal Komunikasi Visual, 2018)
Jajanan Pasar is a term for Indonesian traditional snacks, a part of Indonesian culture that has been forgotten by the young generation. Three-dimensional (3D) animation and Augmented Reality (AR) can be used as a medium for introducing this culture to children aged 4 to 6. Because, in AR, visual between real and digital world can be altered, so the visual of 3D models can be enjoyed from various sides. This study focuses on 3D visualization for AR that packaged in 5 set of puzzles. Each piece has an illustration of the ingredients for making 5 kinds of Jajanan Pasar, after all, puzzle pieces of each set get arranged, a new 3D model of traditional snacks will be appeared. The data was collected using literature and existing studies method. The purpose of this study is to create an optimal 3D visualization for AR that will be applicated for mobile devices. Conclusion from this project are the polygon count and target marker’s quality, affect the appearance of the 3D model in AR form.